Irradiação UV-C em cultivares de uvas Niágara branca, Trebbiano, Isabel e Cabernet sauvignon - Treptow, Taísa Ceratti (2012)
This study evaluated the UV-C irradiation in tissues of rachis with and without berries, and berries with stems of Vitis vinifera and Vitis labrusca. In berries of cv. Isabella, the volatile compounds were analyzed on days 2, 5 and 10 of storage at 20 ºC and the effect of UV-C irradiation on the 5th day of storage. The experiments were based on four treatments of UV-C radiation (0, 1, 2 and 3 kJ m-2) with four cv. (Niagara white, Trebbiano, Cabernet sauvignon and Isabella) and evaluation times (three in berries and four rachis). The rachis with and without berries and the berries with stems remained stored at 20 ºC to evaluate physiological parameters. Ethylene production rate, respiratory rate and total polyphenols were evaluated in all tissues. Only in the rachis was determined by weight loss on days 1, 3 and 5, reducing sugars, non-reducing sugars on the 5th day. Berries and the juice from the cv. Isabella the 5th day of storage at 20 °C the total soluble solids (TSS), titratable acidity (TA), anthocyanins, total phenols, sugars and the ratio (TSS/ TA) were measured. In berries of cv. Isabella on days 2, 5 and 10 storage and berries irradiated with UV-C in amounts of 0, 1, 2 and 3 kJ m-2, volatiles were extracted by solid phase microextration. After desorption, the volatile compounds were separated by gas chromatography, identified by mass spectrometry and quantified by flame ionization detector. For the sensory analysis of the juice discriminatory tests for paired comparison of difference and test ranking were used. The physiological response of UV-C irradiation depends on the cv. and the irradiated tissue. Only the rachis of grape Vitis labrusca ‗Niagara white behaves climateric during storage in post-harvest and may reduce the self life of table grapes. This study found a possible hormetic dose of 3 kJ m-2 only for the cv. Isabella berry. 84 volatile compounds were detected over the days of storage. After 5 days storage, berries irradiated with UV-C 66 volatiles were found. And the dose of 3 kJ m-2 increased the concentration of esters and aldehydes, and 43,8% increase in the total polyphenols in berry. In the paired comparison test of difference, the judges showed greater intensity in the aroma of the juice from grapes irradiated. In the ranking test, the judges were unable to discriminate between different doses of irradiation, though differing dose control (0 kJ m-2) of the irradiated treatments. The analytical test enabled by gas chromatography to determine statistical differences between the different doses detected volatiles, especially at a dose of 3 kJ m-2, in which panelists found no difference.